The Pan-African Investment Code a good first step, but more is needed - Mouhamadou Madana Kane (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2018)
Achieving Africa's structural transformation requires adopting an investment policy framework that promotes FDI while protecting the interests of African countries. The Pan-African Investment Code is an important step in this direction, but its non-binding character calls for influencing the content of other regional instruments to achieve greater impact.
Keywords: 330